INVESTIGATING A NEW METHOD IN PATTERN MAKING USING SIMPLIFIED TECHNIQUE IN ISLAMIC WEAR - Kamarulzaman Saidi; Azwady Mustapha; Norzaleha Zainun; Nasyirah Saleh (Journal of Islamic, Social, Economics and Development, 2022)
Drafting pattern is the foundation in of creating garment. Therefore, the aim of this research is to find method and formula in creating flat pattern drafting for the women that are friendly, and can be great contribution to designers and students in saving times and yet getting a perfect cut and fit for female outfits. Hence, there are two objectives in this research. First, construct a simplified and effective in pattern drafting method, with have two darts in front bodice and one dart at the back bodice, which is same with the result given by author of Metric Pattern Cutting, Winifred Aldrich, which her method also got two arts in front bodice and one dart at the back bodice. Second. To offer a formula in flat pattern drafting which is accurate time saving and easy to follow. This particular method can be applied in a small and medium industries, fashion houses, boutiques, colleges, universities and people who have desires for making their own outfits. The offering of formula in pattern drafting in flat pattern which accurate time saving and easy to follow, then also to construct a simplified and effectiveness in pattern drafting method. That formula was having two darts in front bodice and one dart at the back bodice, which same with methods from Metric Pattern Cutting books. They are five stages of methodologies into doing this research. They are first stage, from researcher observation, identification and investigation of researcher area. Second stage collection of related literature and secondary data was collected from magazine, books and entire internet. Third stage analyzed information from interviewer and then feedback analysis. Fourth stage the comparison of five drafting method was from measurement, draft, cut, fitting and lastly finding. Fifth stage is modified method and final toile was to compare between the researcher method and from Metric Pattern Cutting methods. As the result from these comparisons, according from Metric Pattern Cutting method takes eight hours and fifteen minutes to finish the toile starting from drafting pattern, sewing and fitting onto toile. While from researcher method takes five and half hours and fifteen minutes. However, from researcher methods has less alteration with the toile. As the conclusion, the researcher found that the Metric Pattern Cutting learned is complicated and difficult to memorize and it is time-taking as, compare to the pattern drafting method offered by the researcher. All of the objectives had been met. Hypothesis are found to be through in this research are truth. According from the Metric Pattern Cutting has the complicated and difficult to memorize steps, very time consuming and many alterations. However, method from the researcher has a perfect fitting and less alteration. As far as fitting of the sample muslin (toile) the researcher block had shown a better fitting as compared to Winifred Aldrich books.